Geländemodellierung für Landschaftsarchitekten und Architekten : landscapingSMART3D-Machine Control SystemsStormwater Management. - Petschek, Peter (De Gruyter, 2014)
Grading is an important aspect of landscape architecture. The book explains the basics such as contour lines, land forms, earth mass calculation, and introduces the topics of slope protection systems, rainwater management, or grading for roads and parking lots. In the 2nd edition is updated with new digital technologies including landscapingSMART, DTM and 3D machine control. Practical examples and exercises complement the theoretical foundations.